2018
DOI: 10.14710/jitaa.43.4.352-360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of live weight on libido, sperm quality, testosterone and lute-inizing hormone in replacement stock of Ongole Grade bull

Abstract: The objective of this study was to determine the effect of live weight (LW) on libido, sperm quality, testosterone, luteinizing hormone (LH) in Ongole grade (OG) bull. This study used 32 heads of OG bull with a completely randomized design that were divided to four different LW groups, i.e. group I was 170 to <210kg, group II was 210 to <250kg, group III was 250 to <290kg and group IV was 290 to 330kg. Parameters: observed were libido, testosterone hormone, LH, and semen quality. Data were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
8
0
4
Order By: Relevance
“…Libido levels in this study were similar to studies comparing levels between Kiko and Boer breeds, with no significant difference (P> 0.05) (Ford Jr et al 2009). Previous studies show that libido scores vary more among some animals (Rhen and Crews 2002;Younis et al 2003;Ahmad et al 2005;Kondracki et al 2013;Affandhy et al 2018). Therefore, the libido levels obtained in this study indicate no significant differences based on breed.…”
Section: Libidosupporting
confidence: 53%
“…Libido levels in this study were similar to studies comparing levels between Kiko and Boer breeds, with no significant difference (P> 0.05) (Ford Jr et al 2009). Previous studies show that libido scores vary more among some animals (Rhen and Crews 2002;Younis et al 2003;Ahmad et al 2005;Kondracki et al 2013;Affandhy et al 2018). Therefore, the libido levels obtained in this study indicate no significant differences based on breed.…”
Section: Libidosupporting
confidence: 53%
“…Average serum testosteron level found in this study was relatively similar to those reported in Ongole crossbred cattle, 7.0 ± 0.8 ng/ml [18], but slightly higher than those found in Simmental bull 6.1 ± 0.4 ng/ml [18], Friesian Holstein (FH) bull aged 3 -4 years old 2.07 ± 1.12 ng/ml [13], and adult FH bulls 5.66 ± 1.08 ng/ml [10]. Variation of blood testosterone levels might caused by many factors such as breed, climate, rations and age [19,20,21,22] as well as sensitivity and accuracy of measurement methods used [23]. [25]improved body condition or bodyweight will give a response to enlargement of scrotal size.…”
Section: Serum Testosterone Levels In Aceh Bullsmentioning
confidence: 98%
“…The greater scrotal and testicular traits indicate that the bulls have high sperm production capacity. In addition, the bulls with greater body weight also had a higher luteinizing hormone (LH) concentration (Affandhy et al, 2018). LH is one of the most crucial hormones in spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%